RESPONSE EVALUATION OF THREE OLIVE CULTIVARS TO THE IN VITRO CULTIVATION UNDER DIFFERENT LIGHT WAVELENGTH AND THE EFFECTS OF THE COMBINATION BETWEEN ZEATIN AND GIBBERELLIC ACID - DONINI, Lorena Pastorini; SCHUCH, Márcia Wulff; RIBEIRO, Mirian de Farias; SOUZA, Joseane Almeida de; SOARES, Gustavo Campos (Scientia Agraria, 2008)
Usually olive propagation is done by hardwood cuttings; however cutting viability is dependent of innumerous factors. Therefore, tissue culture may be a good alternative to propagate this specie. Two experiments were carried out aiming to establish in vitro three olives cultivars under different light conditions and evaluate the zeatin and gibberellic acid combination on in vitro establishment of the olive tree cultivar Koroneiki. In the first experiment it was used nodal segments of three olives cultivars (Picual, Frantoio and Koroneiki) and different light quality (fluorescent, red, blue and green). They were cultivated into medium MS + 8.8 umol L-1 BAP + 4.33 umol L-1 GA3 + 0.49 umol L-1 IBA. ‘Frantoio’ showed the highest oxidation rates at the 21st and 28th days of cultivation. The fluorescent light provided the highest survival percentage and among cultivars ‘Koroneiki was superior to others. Regarding to establishment it was observed that the fluorescent light was greater for ‘Koroneiki’ and did not differ from green for ‘Picual’. It was not observed bacterial contamination and the fungal contamination did not present statistics differences. At the second experiment nodal segments of ‘Koroneiki’ were cultivated in culture medium containing different zeatin concentrations (10 e 20 umol L-1) combined or not with 10 umol L-1 GA3. The addition of zeatin and gibberellic acid into the culture medium was not efficient for the in vitro establishment of olive cultivar Koroneiki. As there was not difference between zeatin concentrations the use of 10 umol L-1 is sufficient and provides reductions of laboratorial costs.